Respuesta :
f(x)=2x(2)−96
Step 1: Add -4x to both sides.
xf+ −4x = 4x−96+ −4x
xf −4x= −96
Step 2: Factor out variable x.
x(f−4)= −96
Step 3: Divide both sides by f-4.
x(f−4)/ f−4 = −96/ f−4
x= −96/f−4
Answer:
x= −96/ f−4
Step 1: Add -4x to both sides.
xf+ −4x = 4x−96+ −4x
xf −4x= −96
Step 2: Factor out variable x.
x(f−4)= −96
Step 3: Divide both sides by f-4.
x(f−4)/ f−4 = −96/ f−4
x= −96/f−4
Answer:
x= −96/ f−4
Answer:
[tex]x=\pm 4\sqrt{3}[/tex]
Step-by-step explanation:
We have been given an equation [tex]f(x)=2x^2-96[/tex]. We are asked to solve for x.
To solve for x, we will equate our function with 0 as:
[tex]2x^2-96=0[/tex]
[tex]2x^2-96+96=0+96[/tex]
[tex]2x^2=96[/tex]
[tex]\frac{2x^2}{2}=\frac{96}{2}[/tex]
[tex]x^2=48[/tex]
Upon taking square root of both sides, we will get;
[tex]\sqrt{x^2}=\pm \sqrt{48}[/tex]
[tex]x=\pm \sqrt{48}[/tex]
Factor out perfect square from square root:
[tex]x=\pm \sqrt{16\cdot 3}[/tex]
[tex]x=\pm \sqrt{4^2\cdot 3}[/tex]
[tex]x=\pm 4\sqrt{3}[/tex]
Therefore, the solution of our given equation is [tex]x=\pm 4\sqrt{3}[/tex].